Evaluation of Factors Influencing Assistant Referee Decisions in Determining "Offside" in Football - Anatoly Abdula; Stanislav Marulin (Слобожанський науково-спортивний вісник)
Background and study aim. The human factor and referee errors are an inherent part of football. The number of mistakes can be significantly reduced, but it cannot be completely eliminated. At the same time, we must understand the nature of the error, what exactly influences the occurrence of the mistake, which part of the error is a subjective factor, and which part is an objective factor that is less susceptible to correction and does not depend on the referee's practice, experience, and training. This study is based on the procedure and factors that influence decision-making in the context of Law 11 (Offside). Decisions regarding the "offside" position are made by assistant referees and are among the most complex and discussed topics among experts and fans. The goal of the study is to determine the factors influencing the assistant referee's decisions when determining "offside" in football.